Radwa Ashour's Granada Trilogy as a deconstructive text - Taghreed Rabie; Abdulgawad Elnady; Hany Helmy (International Journal of Advanced Humanities Research)
This study aims at displaying how Radwa Ashour links both past and present and makes use of memories and the lost glory of regaining Andalusia to deconstruct the Arabs' loss in releasing Palestine and restoring Jerusalem. It displays Derrida's deconstruction as a way to make a deeper reading of Ashour's masterpiece entitled Granada trilogy as a deconstructive text. To achieve this, the researcher will highlight the sentimental history of the Arabs' relationship with Andalusia and that of Palestine. Then, it will be shown how both Andalusia and Palestine are lost and the great pain the Arabs feel because of their utmost recognition of both nations. The researcher will also observe how deconstruction gives hope for all Arabs to start all over again by making an implied comparison between the similar conditions of both occupied nations after their glorious conquest. Furthermore, the research will emphasize the effect of the author as an Arab feminist in portraying her female characters in the Granada trilogy which consists of three novels entitled Granada (2003), Maryama (1995), and w-al-Raḥīl (1995). Radwa Ashour (1946-2014) is a feminist, writer, translator, literary critic, and university professor. She was born to a family with a literary background. Her Political standpoints are a fundamental part of her academic career. She wrote Siraaj, Granada trilogy, Heavier Than Radwa, and The woman from Tantoura. She also wrote two short story collections and five criticism books. Granada was chosen as one of the best Arabic novels of the 20th century.